Improving the Quality of History Teaching in Non-Historical Specialties and Training Programmes through Systematic Implementation of the Historicism Principle - Elena N. Dyatlova (Вестник Московского Университета. Серия 20: Педагогическое образование)
Background. The presented study analyses modern approaches to teaching history in the system of higher education. The scientific search is due to the demand of the state and society to improve the quality of historical education, which acts as a resource for solving the problems of forming patriotic and civic consciousness among the younger generation.